2018
DOI: 10.1016/j.fsi.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Cyprinid viral diseases and vaccine development

Abstract: In the past decades, global freshwater fish production has been rapidly growing, while cyprinid takes the largest portion. Along with the rapid rise of novel forms of intensive aquaculture, increased global aquatic animal movement and various anthropogenic stress to aquatic ecosystems during the past century, freshwater fish farming industry encounter the emergence and breakout of many diseases, especially viral diseases. Because of the ability to safely and effectively prevent aquaculture diseases, vaccines h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 183 publications
(260 reference statements)
0
49
0
Order By: Relevance
“…According to the OIE-Wahis system, there were nine outbreaks from November 2018 to late April 2019 in Iraq [ 17 ]. Moreover, between 2018–2019, the OIE-Wahis interface [ 17 ] (accessed on October 28th, 2019) reveals that KHVD was reported in Africa, Europe, and North America, an occurrence which might be connected with the global fish trade [ 1 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the OIE-Wahis system, there were nine outbreaks from November 2018 to late April 2019 in Iraq [ 17 ]. Moreover, between 2018–2019, the OIE-Wahis interface [ 17 ] (accessed on October 28th, 2019) reveals that KHVD was reported in Africa, Europe, and North America, an occurrence which might be connected with the global fish trade [ 1 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under a changing environment, disease risks to both the marine environment and aquacultured species are also likely to change. Longer summers will provide a wider window for pathogen outbreaks (Gubbins et al 2013;Jensen & Kristoffersen 2015;Lyngstad et al 2018;Su & Su 2018). This could cause changes in the epidemiology of endemic and exotic diseases in Maine, resulting in a longer period when aquacultured organisms will be at risk of infection.…”
Section: Emerging and Established Diseases In Finfish Aquaculturementioning
confidence: 99%
“…Grass carp reovirus (GCRV), a dsRNA virus, causes severe hemorrhagic disease in juvenile grass carp (Ctenopharyngodon idella) and black carp (Mylopharyngodon piceus) (24)(25)(26). Our previous research demonstrated the important roles of grass carp TLR22 in response to GCRV infection.…”
Section: Introductionmentioning
confidence: 99%